Diseño de un sistema de gestión por procesos al servicio de atención de adultos mayores en el hogar gerontológico Años Dorados. - Hidalgo Nacimba, Adriana Mishell (2021)
The "Gerontological Home Golden Years", as part of its growth policy, framed in the quality of service provision to its residents, sees the need to incorporate a design of a process management system to the care service for the elderly. The research project starts from the need to manage, execute and control the activities ruled by the Ministry of Social Economic Inclusion (MIES), which is the entity in charge of regulating its operation. For the design of the process management system, the analysis of the internal situation of the organization was carried out in the first instance, allowing to enter into context with the activities developed, the processes of each area were digitized and normalized, once the processes were identified through the quality sheet, performance indicators were established, which allowed identifying the degree of compliance with the functions of each area. For the continuity of the design, the improvement plan was developed where the areas with the highest rate of non-compliance were prioritized, a process map was prepared which allowed collecting the interrelation of all the processes that are developed, the process manual recorded the steps, procedures and responsible, improving the development and fulfillment of the functions of all the personnel and finally, for the control of the process management system, the Deming cycle was established, allowing continuous improvement in its activities. For the collection of information, the inductive methodology was applied, allowing the collection of information necessary for the development of the titling work, by complying with the project, a positive impact is obtained in the economic, social and environmental spheres. At present, the gerontological center was audited by the technical staff, in charge of gathering information and applying the evaluation sheet, obtaining a score of 70/101 points, through the implementation it is intended to achieve a score higher than 86/101 points. In its next audit, when designing the process management system, it is possible to manage and control the processes, sub-processes and activities of each area, in addition to contributing to the fulfillment of the institutional objectives imposed by the management.